Performance of holstein cows fed wet corn gluten feed or soyhull-steep liquor pellets during early lactation - Ferdinand, E.E.; Titgemeyer, Evan C.; Park, A.F.; DeFrain, J.M.; Shirley, John E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Wet corn gluten feed and soyhull-steep liquor pellets tended to increase dry matter intake and milk yield. Combining condensed corn steep liquor with raw soybean hulls provides a convenient source of digestible fiber and rumen degradable protein.
Keywords: Dairy; Wet corn gluten feed; Soyhulls; Corn steep liquor